The effects of psychological inoculation on cognitive barriers against condom use in women with HIV: A controlled pilot study (2011)
Past studies have shown that in attempts to prevent HIV, health education yields little change in condom use. The reason may be that education fails to target barriers for changing behaviour. The present controlled pilot study tested whether psychological inoculation (PI) reduces such barriers for using male condoms. Twenty-two Nigerian women with HIV were randomly assigned to receive PI or health education (control). In the PI condition, women learned to refute sentences reflecting barriers against condom use, while controls learned how to use condoms and the consequences of their non-use. Barriers for condom use, self-efficacy to negotiate condom use with partners and actual condom use were self-reported before and one week after interventions. Results revealed that only in the PI group were there statistically significant increases in condom use negotiating self-efficacy and reductions in barriers concerning motivation, sexual satisfaction and partners. Controls reported no statistically significant changes. However, actual reported condom use was unchanged in both groups. Thus, it is feasible to conduct PI interventions in an African sample of HIV patients. Furthermore, PI can reduce cognitive barriers for condom use, while health education yields little changes in such outcomes over time. If replicated in larger samples with longer follow-ups, these findings could eventually have implications for HIV prevention in several world regions.